Analysis of Packaging Machine at PT. Dunia Kimia Jaya Gresik Using Overall Equipment Effectiveness and Fault Tree Analysis - Farich Maulana, Muhammad; Jufriyanto, Mohammad (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study evaluates the effectiveness of a Sodium Metabisulfite (SMBS) packaging machine at PT. DKJ using Overall Equipment Effectiveness (OEE) and Fault Tree Analysis (FTA). OEE was employed to assess machine performance through availability, performance, and quality indicators, while the Six Big Losses framework was used to identify major sources of productivity loss. Furthermore, FTA was applied to determine the root causes of dominant losses affecting machine effectiveness. The study utilized production data, direct observations, interviews, and company records collected from December 2024 to May 2025. The results indicate that the average OEE value of the packaging machine was 63.26%, significantly below the international benchmark of 85%, with low availability and performance as the primary contributors. Six Big Losses analysis revealed that breakdown losses and setup and adjustment losses were the most dominant factors. FTA identified component failure, inadequate preventive maintenance, operator-related errors, and complex setup procedures as the main root causes. This study proposes structured preventive maintenance, operator training, standardized operating procedures, and improved production–material coordination to enhance machine effectiveness and ensure sustainable production performance.